2017
DOI: 10.1111/1365-2435.12949
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and functional effects of fungal endophytes on wood decomposition

Abstract: Abstract1. Despite the central role of saprotrophic fungi in wood decomposition and terrestrial carbon cycling, the diversity and functioning of wood endophytes (i.e. fungi that asymptomatically colonize living plant tissue) on decay remains poorly understood.2. In a 4-year field experiment in a boreal forest in the upper midwestern United States, we investigated whether endophytes influenced fungal community structure and subsequent wood decomposition via priority effects. We compared decay of sterilized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 77 publications
(114 reference statements)
2
30
0
1
Order By: Relevance
“…Distinct fungal assemblages across tree species may drive divergent decay trajectories if they impact the establishment and activity of subsequently arriving wood decay fungi by exerting priority effects (Fukami, ). Consistent with this reasoning, wood endophyte communities have been shown to impact the community assembly and function of subsequently arriving saprotrophic fungi by producing a range of bioactive exudates (Cline, Schilling, Menke, Groenhof, & Kennedy, ; Heilmann‐Clausen & Boddy, ).…”
Section: Discussionmentioning
confidence: 91%
“…Distinct fungal assemblages across tree species may drive divergent decay trajectories if they impact the establishment and activity of subsequently arriving wood decay fungi by exerting priority effects (Fukami, ). Consistent with this reasoning, wood endophyte communities have been shown to impact the community assembly and function of subsequently arriving saprotrophic fungi by producing a range of bioactive exudates (Cline, Schilling, Menke, Groenhof, & Kennedy, ; Heilmann‐Clausen & Boddy, ).…”
Section: Discussionmentioning
confidence: 91%
“…Given our ground‐biased understanding of decomposition, these findings demonstrate the need for holistic studies of decomposition that consider community assembly in suspended debris and its consequences for future ground‐level decomposition (i.e. priority effects; Cline, Schilling, Menke, Groenhof, & Kennedy, ; Osono, ).…”
Section: Discussionmentioning
confidence: 94%
“…Despite its advantages, our approach also limited the scope of organismal effects on decomposition. By sterilizing substrates, we excluded the saprotrophic and priority effects of microbiota that colonize plant matter before decomposition begins (Cline et al, ; Osono, ). We also did not account for invertebrate decomposition, and despite evidence that canopy‐level decomposition is controlled by micro‐organisms (Law et al, ), it is possible that invertebrates influenced the patterns reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that other root-and foliage-associated DSEs will utilize a wide spectrum of substrates (15, 16). Thus, latent saprotrophy may be widespread among DSEs including, at least in the initial stages, the decomposition of forest litter (47), twigs (48, 49) and logs (50). Considering this enormous carbon pool (51), DSEs likely play an important role in the carbon cycle and merit consideration in current ecosystem models (5254).…”
Section: Resultsmentioning
confidence: 99%